DETERMINANT ANALYSIS ON FACTORS AFFECTING MUZAKKI'S TRUST IN AMIL ZAKAT - Mawarni, Yonanda Adelia Tasya; Setiawan, Firman (STAI Asy-Syukriyyah, 2024)
This research aims to analyze the factors that influence muzakki's trust in amil zakat. This type of research is quantitative. The population in this study were muzakki who started paying zakat in 2022 to 2024 which amounted to 19.503 muzakki. While the sample in this study amounted to 100 respondents. The data used in this study are primary and secondary data. This research data collection technique uses a questionnaire distributed via google form. The data analysis test uses partial least square analysis through smartpls 4.0 software. Based on the results showed that accountability has no significant effect on muzakki trust. Transparency variables, service quality and amil competence have a significant effect on muzakki trust. While the accountability variable through transparency has a significant effect on muzakki trust.